Implementasi Undang-Undang Tindak Pidana Kekerasan Seksual Terhadap Perlindungan Hak Korban Dan Penguatan Asas Non- Diskriminasi - Aprianti Lubis; Zasmita Maulia Sari (CV. ITTC INDONESIA, 2024)
Sexual violence has become one of the crucial problems in Indonesia. This study aims to understand the regulations governing criminal acts of sexual violence and how they are implemented in protecting victims' rights and strengthening the principle of non-discrimination. with cases that continue to increase every year. This study is a juridical-normative study. The results show that the protection of victims' rights in cases of sexual violence, although clearly regulated in the TPKS Law, still faces various obstacles. And the implementation of the principle of non-discrimination in Law no. 12 of 2022 concerning criminal acts of sexual violence (UU TPKS) plays a crucial role in ensuring that every victim of sexual violence, regardless of social, economic, cultural, or other identity background, receives equal legal protection.